Latin America's external indebtedness - Jürgen Westphalen (Intereconomics, 1977)
Latin America's foreign debts have been mounting fast in the last ten years. The following article shows that it would nevertheless be wrong to suggest that Latin America has generally run up excessive debts.
Keywords: 330; Latin America